Improving Fourth Grade Students’ Critical Thinking Skills with MIKIR Approach - Mahmud Alpusari; Eva Astuti Mulyani; Neni Hermita; Elpri Darta Putra (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2020)
This study aims to evaluate the implementation of an approach to improve elementary school students’ critical thinking skills. The approach is called MIKIR that stands for mengalami (experiencing), interaksi (interaction), komunikasi (Communication), internalisasi (internalization), and refleksi (reflection). This research was conducted at a public elementary school in Pasir Penyu District, Indragiri Hulu Regency, Indonesia. The subject of this research was 23 fourth grade students. The method used in this research was quasi-experimental method. The experimental design used in this study was pre-test and post-test one group design. The results of the study obtained an average pretest score of 22.13 and an average posttest score of 27.70 from a maximum score of 36. Based on these results, the score increased by 5.57 points or 20.10%. The overall average N-gain value of 0.41 with moderate criteria, so that the MIKIR approach can improve fourth grade students’ critical thinking skills. This result was supported by the results of student learning activities and student responses to learning with the MIKIR approach obtaining an average of 84.6% with a very good category.